The use of the information and communication technologies ICTs) as a language learning strategy by first-year students, of the b.a. in Modern Languages Specialization in French and English, semester I- 2019 at The University of El Salvador - Ostorga Garcia, Stefany Cristina; Rosales Jandres, Martha Esther; Trejo Alfaro, Tatiana Ivonne (2024)
The Internet has grown without borders, without limits, and it has opened doors where all technologies have been able to grow. The Information and Communication Technologies (ICTs) are a consequence of the developments in the telecommunications, engineering and all technological upgrades. Over the years, society has undergone changes that are adopted through the process of socialization, in which globalization is on the way, and few countries have fallen behind in terms of technological advances, El Salvador is one of them, as these technologies serve as a tool for the universalization of technical advances. Now, it is difficult for the new generations to remember what the world was like and specifically in El Salvador prior to the arrival of the internet. Today, different situations or moments of life are developing in the virtual world; most of its users are young, whether they are studying basic education, high-school or college. Likewise, the growth in the access of Information and Communication Technologies (ICTs) is transforming the learning processes in students. ICTs have become within a short time one of the basic building blocks of a modern society; a number of websites where students can find different types of information have emerged to help them develop their academic activities and thus learn more. ICTs –and the Internet in particular–provide language learners with the opportunity to use the language that they are learning in meaningful ways in authentic contexts. The Internet provides an easy and fast access to the use of current and authentic materials in the language being studied, which is motivating for the language learner (Fitzpatrick, 2019). Such authentic materials include, for instance, online newspapers, webcasts, podcasts, newsroom video clips or even video sharing websites such as YouTube. Another motivating language learning opportunity using ICTs is provided by chat rooms and virtual environments where the language learner can practice not only the written use of the language, but also practice speaking and pronunciation, without the fear of making mistakes. The University of El Salvador, as a social institution, is providing to the new generations the technological tools to become an active and productive part of the new society immersed in continuous expansion of its cultural and commercial trades. In this respect, as students of the Foreign Language Department, the research group wants to investigate what use first-year students make of the Information and Communication Technologies (ICTs) as a mechanism of improvement of their language learning strategies.